The effectiveness of in-service training "pharmacopeia home health" based on Kirkpatrick's model: A quasi-experimental study - Mahtab Firooznia; Amir Hamta; Sareh Shakerian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Assessing the effectiveness of in-service training courses in order to achieve the desired goals and reduce the waste of costs and opportunities in the system is necessary. The purpose of this study was to determine the effectiveness of the "pharmacopeia home health" course considering its importance in different aspects using the Kirkpatrick model. MATERIALS AND METHODS: The present study was a quasi-experimental conducted at community health workers (CHWs) on three levels of reaction, learning, and behavior. In each phase, a valid questionnaire was used to measure the outcome according to the Ministry of Health guidelines with pretest and posttest measurements. The data were analyzed through SPSS 23, using descriptive statistics and repeated measures test and general linear model. RESULTS: The results of the study showed that at the level of reaction in terms of content and holding, conditions of implementation were favorable. Findings at the level of learning showed that the training course was only effective in enhancing the knowledge and awareness about drug maintenance and had no significant effect on other areas. In the third level, the results of the CHWs' performance showed that in some areas, the results were influenced by the demographic variables. CONCLUSION: The present study showed the effectiveness of education in different areas using on the Kirkpatrick model. Given the lack of impact of education in some areas in the present study and on the other, it is necessary to consider cooperative learning methods in order to develop the effectiveness of the courses.